EVALUATE THE EFFECTIVENESS OF CAPSAICIN CREAM ON PATIENTS WITH HERPES ZOSTER AT 19-8 HOSPITAL (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the treatment effectiveness of capsaicin cream on patients with herpes zoster.Subjects and methods: This was a controlled retrospective, prospective study of patients with herpes zoster treated at 19-8 Hospital from 16 January 2025 to 9 December 2025Results: The study populations were divided into two groups: a group treated with capsaicin (30 patients) and a control group (30 patients). There were no differences in age, gender, symptoms, or severity of herpes zoster between the two groups before treatment. After treatment, the capsaicin group had a significantly higher pain relief rate (76.7% vs. 3.3% without pain) and a higher patient satisfaction rate (100% vs. 83.3% with a very satisfactory complaint) than the control group.Conclusion: Capsaicin cream demonstrated promising efficacy and safety in reducing patients' symptoms and improving their quality of life.
Keywords: herpes zoster, capsaicin cream